Zastosowanie fenomenologii „moralnego wzlotu” Maxa Schelera do analizy przywództwa - Bombała, Bronisław (Annales. Etyka w Życiu Gospodarczym, 2012)
Phenomenology of management seeks to grasp the essence of manager's work – its core is the analysis of leadership. Phenomenology of leadership is an approach that makes the idea “to be someone – to do something” becomes the guiding principle of of management. Max Scheler’s “moral flight” phenomenology is one of the most important inspiration in the analysis of leadership. His anthropology reveals that being a man is in fact a continuing task that is impossible to take, and the result depends on the man himself. Scheler’s phenomenology is a good way to discover the essence of leadership (eidos) in the process of culture change. This article presents a case study: Ricardo Semler’s inner transformation, who might overcome the technocratic attitude and make the “moral flight”. The main inspiration for him was a metaphor “builder of cathedrals”. As a result of his own inner transformation has become a “builder of cathedrals”, such as a leader, who serves – it was a condition for conversion of others in the “cathedral builders”. As a result of the Semler's “moral flight” their company was transformed in “cathedral builders” guild – community of work.